SOSIALISASI AGENDA PELATIHAN PENGEMBANGAN KEMAMPUAN KOMUNIKASI BERBAHASA INGGRIS - Suparlan, Suparlan; Rizal, Samsul; Hidayatullah, Muh. Roni; Masyudi, Masyudi (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
The team of lecturers from the Institut Pendidikan Nusantara Global did socialization activities for the development of English language skills for the second class of MTs Darul Aminin NW Aikmual Lombok Tengah in order to fulfill one of the Tridharma elements of higher education in the field of community service. English grammar or grammar with Simple Present Tense material as a reference in developing English language skills in this community service. There were 35 students at MTs Darul Aminin NW Aikmual, all of whom came from class A. Each student had difficulties, especially in understanding the Simple Present Tense material, which was proven by the results of the pre-test. Efforts to develop English skills include a pre-test, discussion of material, games, practice questions, and post-test. Besides students being able to use sentence forms properly and correctly, students can also understand Simple Present Tense sentence forms with a new learning atmosphere and more fun learning methods and this is the result of this community service agenda.